Evaluasi Sistem Informasi Kepegawaian Dengan Standar ISO/IEC 9126 Pada Universitas Jambi - Simatupang, John Devin Junior; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2024)
In the current era of globalization, information technology or software is one of the important resources for an institution or organization. Data processing in software as a strategic decision-making tool must be supported by quality information systems and software. One of the information systems or software that functions to assist management processes is the Human Resource Management Information System. The quality of this system has a significant impact on the quality of the information generated. The data collection method used a questionnaire and the data analysis used quantitative descriptive analysis. The results of the data analysis show that the average value of Functionality is 3.97, Usability is 3.62, Reliability is 4.11, Efficiency is 3.87, Maintainability is 3.63, and Portability is 3.79. In general, the software has shown good performance or can be categorized as "Strong" in each analyzed characteristic.In the current era of globalization, information technology or software is one of the important resources for an institution or organization. Data processing in software as a strategic decision-making tool must be supported by quality information systems and software. One of the information systems or software that functions to assist management processes is the Human Resource Management Information System. The quality of this system has a significant impact on the quality of the information generated. The data collection method used a questionnaire and the data analysis used quantitative descriptive analysis. The results of the data analysis show that the average value of Functionality is 3.97, Usability is 3.62, Reliability is 4.11, Efficiency is 3.87, Maintainability is 3.63, and Portability is 3.79. In general, the software has shown good performance or can be categorized as "Strong" in each analyzed characteristic.